Mexico : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This Selected Issues paper analyzes the sources of Mexico's economic growth since the 1960s, and compares various decompositions of historical growth into trend and cyclical components. The role of the implied output gaps in the inflation process is assessed. The paper presents medium-term paths for GDP based on alternative productivity growth rates. The paper also describes the significant steps Mexico has taken to strengthen the structure of its public debt in recent years, both in terms of currency composition and maturity.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet